Internet censorship detected in Tanzania (Tanzania) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Tanzania. Data sourced from CensoredPlanet.
Censorship Incident ID: TZ-2026-0033. Severity: warning. Confidence: 65%